Reproductive potential of the female and productive parameters of the suckling piglet of the cerdo pelon mexicano - Angel-Hernández, Arturo; García-Munguía, Carlos Alberto; García- Munguía, Alberto Margarito; Gutiérrez-Chávez, Abner Josué; Valencia-Posadas, Mauricio; García-Munguía, Argelia; Segura-Correa, José Candelario (Ecosistemas y Recursos Agropecuarios, 2022)
The objective of the research was to know the behavior and maternal ability of the Cerdp Pelon Mexicano (CPM) through the analysis of reproductive and productive parameters from birth to weaning. Two ecotypes of CPM from Huehuetla, Hidalgo (CPH) and from Atlequizayán, Puebla (CPP) were evaluated. The variables per piglet were birth weight (PN) and weaning weight (PD). No dystocia, no deaths were recorded in the deliveries and they presented nesting; the CPP ecotype presented the highest number in reproductive parameters than CPH. The means of the PN and PD were higher for the CPH than CPP piglets. Maternal behavior was favorable, since there were no deaths at birth or in lactation. Regarding the productive parameters, the CPP females had slightly larger litters compared to the CPH, however, the CPH piglets presented a higher weight.